Prevalence and nature of injuries among young professional cricketers of academies and clubs in Lahore; cross sectional survey - Shahzad Akhtar; Danish Hassan; Nazeer Ahmad; Ehtisham Ul Haq (Journal of the Pakistan Medical Association, 2022)
A cross-sectional survey was conducted from February 2021 to June 2021, to assess the prevalence and nature of injuries among young professional cricketers from various academies and clubs in Lahore. The study comprised 149 cricketers representing different academies and clubs of Lahore. Injuries acquired between January and December 2019 were included as retrospective data. The findings revealed that 93 injuries were reported by 149 cricketers with a prevalence of 62.4%. Of these 41 (44%) injuries occurred during matches, 50 (54%) during practice, and 2 (2.1%) injuries were caused during fitness training. The head, neck, and face sustained 3 (3.2%) injuries, while the upper extremities received 35 (37.6%), the lower extremities 39 (41.9%), and the back and trunk 16 (17.2%). The most commonly injured players were fast bowlers 23 (24.7%). First time reported injuries were 66 (70.9%), while those repeated in the past were 16 (17.2%). --Continue